2022
DOI: 10.15567/mljekarstvo.2023.0105
|View full text |Cite
|
Sign up to set email alerts
|

Quality characteristics of ‘Pasta-Filata’ Serbian Kačkavalj cheese and regulatory compliance assessment

Abstract: The purpose of this study was to investigate the chemical, proteolysis, microbiological, colour and textural characteristics of Serbian Kačkavalj cheese in order to determine the variability degree between cheeses, compare their properties to other similar ‘Pasta Filata’ cheeses and to determine if they comply to the regulative requirements. A broad range of variations of cheese characteristics was found among Kačkavalj cheeses. The composition showed high variations: dry matter ranged from 51.52% to 58.71%; f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The results of the study by Satric et al . (2023) showed that in the investigated Kačkavalj cheeses, the L * parameter ranged from 87.25 to 92.08 which is in accordance with the results of our study.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The results of the study by Satric et al . (2023) showed that in the investigated Kačkavalj cheeses, the L * parameter ranged from 87.25 to 92.08 which is in accordance with the results of our study.…”
Section: Resultssupporting
confidence: 91%
“…2023; Satric et al . 2023). In addition to being one of the most popular cheeses, the production stages and characteristics of this cheese are defined by the Institute for Standardization of Serbia through the National Standard for Quality Requirements (Institute for Standardization of Serbia 1997) which gives this cheese a special significance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation